Low Levels of Influenza Vaccine Uptake among the Diabetic Population in Spain: A Time Trend Study from 2011 to 2020 - Zamorano León, José Javier; Jiménez García, Rodrigo; López de Andrés, Ana; de Miguel Diez, Javier; Carabantes Alarcón, David; Albaladejo Vicente, Romana; Villanueva Orbaiz, Rosa; Zekri Nechar, Khaoula; Sanz Rojo, Sara (My University, 2022)
) Background: In this work, we aim to describe influenza vaccine uptake among the diabetic population in Spain to assess the time trend from 2011 to 2020 and identify predictors of vaccine uptake among diabetes patients. (2) Methods: We conducted a descriptive cross-sectional study using the European Health Interview Survey for Spain (2014 and 2020) and the Spanish National Health Surveys (2011 and 2017). The independent variables analysed included socio-demographic characteristics, health-related variables and lifestyle variables. We matched each participant with diabetes with a non-diabetic participant based on age, sex, place of residence and year of survey. (3) Results: The overall coverage among diabetic adults was 52.1% compared to 40.6% for matched participants without diabetes (p < 0.01). The vaccine uptake among adults with diabetes was 52.6% in 2011, 54.38% in 2014 and 53.4% in 2017. The adjusted OR of having been vaccinated in 2020, with respect to 2011, was not significant at 0.87 (95% CI: 0.72¿1.06). Factors such as being male, higher age, being affected by respiratory disease or cancer and being physically active were identified as positive predictors for influenza vaccination uptake, while smoking was a negative predictor. (4) Conclusions: The influenza vaccine uptake is below desirable levels among the adult diabetic population in Spain and has not improved from 2011 to 2020. More efforts should be made to increase influenza vaccine uptake in this high-risk group, especially for women, those aged 18¿64 years, without other high-risk conditions and smokers. Keywords: influenza seasonal; vaccine coverage; diabetes; uptake; trend; Spain